Effectiveness of endoscopic injection of 2% lignocaine in to the bladder wall to control obturator jerk during transurethral resection of bladder tumor (Bangladesh Journal of Urology, 2012)
Purpose- To observe the efficacy of endoscopic injection of 2% lignocaine into the bladder wall at the base of tumor to control obturator jerk. Materials and Methods- This prospective study was performed in Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), National Institute of Kidney Diseases and Urology, Comfort Nursing Home (Pvt. Ltd.) and Lab Aid Specialized Hospital (Pvt. Ltd.) , Dhaka, during the period from January 2009 to December 2009. Total 90 patients were grouped into two on alternate basis. 45 patient in group- A, conducted with endoscopic injection of 2% lignocaine and another 45 patients were in group-B, conducted with nothing to control obturator jerk. Peroperative findings of both groups during transurethral resection are evaluated. Results- In group-A, 45 patients were conducted with endoscopic injection of 2% lignocaine to control obturator jerk, 42 patients (93.3%) developed complete elimination and 3 patients (6.7%) developed partial elimination of obturator jerk. In our series overall response in complete resection of bladder tumor was 100%. In group-B patients were not conducted with 2% lignocaine injection. Statistical analysis was done and result is significant (P